El tema simposíaco en la poesía latina, de Horacio a Marcial I: los elementos externos del simposio - Marina Sáez, Rosa María (Myrtia: Revista de filología clásica, 1991)
In this article is tried to clasify the external patterns of the latin sympotic poetry: convival rules, parfums, garlands and finally music. The finality of this clasification is to stablish the relationship between the use of this patterns in Greek and Roman poetry, relationship so clear that can let to come to the conclusion, following the ideas of authors like G. Williams, that Hellenic literary tradition is more important in this case than a possible influence of real life.